Pareto-improving unemployment policies - Jörg Lingens; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2006)
We investigate how continental European unemployment can be reduced without reducing unemployment benefits and without reducing the net income of low-wage earners. Lower unemployment replacement rates reduce unemployment, the net wage and unemployment benefits. A lower tax on labour increases net wages and - for certain benefit-systems - unemployment benefits as well. Combining these two policies allows to reduce unemployment in countries with net-Bismarck and Beveridge systems without reducing net income of workers or of the unemployed. Such a policy becomes self-financing under realistic parameter constellations when taxes are reduced only for low-income workers.
Keywords: J38; J51; H23; E60; 330; Arbeitslosigkeit; Beschäftigungspolitik; Arbeitslosenversicherung; Theorie